Remodeling the tumor immune microenvironment with oncolytic viruses expressing miRNAs - St-Cyr, Guillaume; Penarroya, Daphné; Daniel, Lauren; Giguère, Hugo; Alkayyal, Almohanad A.; Tai, Lee-Hwa (Frontiers in Immunology, 2023)
MiRNAs (miRNA, miR) play important functions in the tumor microenvironment (TME) by silencing gene expression through RNA interference. They are involved in regulating both tumor progression and tumor suppression. The pathways involved in miRNA processing and the miRNAs themselves are dysregulated in cancer. Consequently, they have become attractive therapeutic targets as underscored by the plethora of miRNA-based therapies currently in pre-clinical and clinical studies. It has been shown that miRNAs can be used to improve oncolytic viruses (OVs) and enable superior viral oncolysis, tumor suppression and immune modulation. In these cases, miRNAs are empirically selected to improve viral oncolysis, which translates into decreased tumor growth in multiple murine models. While this infectious process is critical to OV therapy, optimal immunomodulation is crucial for the establishment of a targeted and durable effect, resulting in cancer eradication. Through numerous mechanisms, OVs elicit a strong antitumor immune response that can also be further improved by miRNAs. They are known to regulate components of the immune TME and promote effector functions, antigen presentation, phenotypical polarization, and varying levels of immunosuppression. Reciprocally, OVs have the power to overcome the limitations encountered in canonical miRNA-based therapies. They deliver therapeutic payloads directly into the TME and facilitate their amplification through selective tumoral tropism and abundant viral replication. This way, off-target effects can be minimized. This review will explore the ways in which miRNAs can synergistically enhance OV immunotherapy to provide the basis for future therapeutics based on this versatile combination platform.